45.4: The White Light‐Emitting Diode Using Organic Material and Perovskite Quantum Dots. (26th August 2021) - Hyeon, Min Woo; Kim, Jungwon; Suh, Min Chul
Abstract : White LED is widely used for large‐area displays and lighting. Here we fabricated the white LED using red and green perovskite quantum dots and blue organic materials. The maximum efficiency of this hybrid white LED device was 2.1 cd/A and has a color coordinate of (0.32, 0.27) which is very close to the required white coordinate of (0.33, 0.33) based on the CIE 1931 color coordinate.